Determination of Ventilation Openings Ratio in Greenhouses under Mediterranean Climate Conditions - Abdullah Nafi Baytorun; Sait Üstün; Adil Akyüz; Derya Önder (Turkish Journal of Agriculture: Food Science and Technology)
Ventilation is one of the methods used to obtain the biological optimal point of environmental factors needed for the plants in greenhouses. In the greenhouses, air change coefficient must be more than 50 h-1 in order to supply effective air ventilation. Temperature differences like air change coefficient can be regarded as a criterion to determine efficiency of ventilation in the greenhouses. In this study, the temperature values were calculated by using energy balance and Bernoulli equation at different ventilation opening ratios (AV/AG) depending on climatic properties in the Mediterranean region (Antalya). If was found that, based on temperature and radiation values of Antalya province, 20% ventilation opening rate is sufficient in the roof area. A temperature difference (∆T) of 1K can be achieved with a 50% shading of radiation and a 20% ventilation opening in June in the Mediterranean region. However, additional cooling is necessary in the greenhouses around noon hours because outdoor temperature is greater than 30°C.